2021
DOI: 10.24200/jonus.vol6iss2pp250-272
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corrective Feedback on Iranian Efl Learners’ Writing Complexity, Accuracy, and Fluency

Abstract: Background/Purpose: Recently, corrective feedback (CF) has gained considerable importance in language teaching research. Up until now, there has been less attention to the use of CF in an Iranian context.  This current study aims at investigating the impact of corrective feedback on Iranian intermediate EFL learners’ Complexity (C), Accuracy (A), and Fluency (F) in their writing production.   Methodology: After administering an Oxford Quick Placement Test (OQPT), the researcher selected 30 Iranian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…In the post-test, the experimental group's performance differed markedly from the performance of control group. The results of the investigation are consistent with those of Ghahderijani (2021), Fatemi andHarati (2014), andNusrat et al (2019), who reported a noteworthy enhancement in treatment outcomes through corrective feedback. However, the fallouts of the investigation partially agree with the outcomes of Subon and Ali (2022) and Hassan et al (2022), which show marginal improvement in EFL learners.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the post-test, the experimental group's performance differed markedly from the performance of control group. The results of the investigation are consistent with those of Ghahderijani (2021), Fatemi andHarati (2014), andNusrat et al (2019), who reported a noteworthy enhancement in treatment outcomes through corrective feedback. However, the fallouts of the investigation partially agree with the outcomes of Subon and Ali (2022) and Hassan et al (2022), which show marginal improvement in EFL learners.…”
Section: Discussionsupporting
confidence: 87%
“…Fatemi and Harati's (2014) study found significant improvements in grammatical accuracy in Iranian university EFL classrooms with corrective feedback. Similar to this, Ghahderijani (2021) found that corrective feedback improves the Complexity, Accuracy, and Fluency (CAF) of Iranian Intermediate EFL learners' writing and concluded that it is useful. According to Subon and Ali's (2022) study, 50 Malaysian ESL students' writing abilities increased considerably as a result of implicit written corrective feedback (WCF) from instructors, which the students perceived to be beneficial.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations